Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Ibu Hamil Trimester Iii Di Wilayah Kerja Puskesmas Beringin Raya Kota Bengkulu Tahun 2024 - Yuspita, Serli; Metasari, Des; Azissah, Danur (Jurnal Multidisiplin, 2025)
In 2021, there were 7,389 deaths in Indonesia. This number represents an increase compared to 2020, which recorded 4,627 deaths (Ministry of Health, 2021). The Indonesian Health Survey (2023) found that 27.7% of pregnant women in Indonesia had anaemia in 2023. The aim of this study was to identify factors associated with the incidence of anaemia among pregnant women in the third trimester in the Beringin Raya Health Centre work area, Bengkulu City, in 2024. The research method used was a descriptive quantitative study with a cross-sectional approach. The sampling technique employed total sampling, with a sample size of 31 participants representing all pregnant women in the third trimester in the Beringin Raya Health Centre Work Area, Bengkulu City, in 2024. The results showed that nearly half of the respondents (35.5%) had anaemia, nearly half of the respondents (41.9%) were of high-risk age (<20 or >35 years), a small proportion of respondents (19.4%) were grandemultigravida, nearly half of the respondents (25.8%) had chronic energy deficiency, and nearly half of the respondents (29%) had insufficient knowledge. The results showed that age (0.021), parity (0.000), chronic energy deficiency (0.012), and knowledge (0.000) were associated with the occurrence of anaemia. There is a relationship between age, parity, KEK, and maternal knowledge with the incidence of anaemia in pregnant women in the third trimester in the Beringin Raya Health Centre Working Area, Bengkulu City. The researchers suggest that the Beringin Raya Health Centre in Bengkulu City use the results of this study as a basis for implementing guidance, training, and counselling programmes on the incidence of anaemia in pregnant women in the third trimester.